A comprehensive integrative perspective of the anaerobic threshold engine - Vasconcelos, G.; Canestri, R.; Cosme Ramos Prado, R.; Brietzke, C.; Franco-Alvarenga, P.; MeirelesSantos, T.; Oliveira Pires, F. (Physiology & Behavior, 2019)
Recently, Sales et al. [1] proposed an integrative perspective of the anaerobic threshold (AT), highlighting peripheral stimuli and autonomic adjustments during exercise. According to their engine [1], the central nervous system (CNS) progressively increases the cardiac output through a complex feedforward coupling response of peripheral organs and muscle s in order to meet the increased metabolic requirement during maximal incremental test (MIT). They argued that the increased sympathetic activity and complete parasympathetic withdrawn at ~60-80% VO2MAX would match an exponential increase in blood catecholamine concentrations and progressively impaired blood and O2 supply to organs and skeletal muscles. This intensity would be coincident with electromyography (EMG) and ventilatory (VT) thresholds. Although the authors are commended for this integrative perspective, it is needed to adequately consider the CNS to provide a comprehensive understanding of the AT puzzle. The role of the prefrontal cortex (PFC) should be highlighted, as PFC is involved in a cascade of integrated physiological events and connects physiological to psychological responses. The present commentary advances Sales' et al. approach [1], expanding their perspective to cerebral and psychological responses.